Co-activator candidate interactions for orphan nuclear receptor NR2E1. (December 2016) - Corso-Díaz, Ximena; de Leeuw, Charles; Alonso, Vivian; Melchers, Diana; Wong, Bibiana; Houtman, René; Simpson, Elizabeth
Abstract Background NR2E1 (Tlx) is an orphan nuclear receptor that regulates the maintenance and self-renewal of neural stem cells, and promotes tumourigenesis.Nr2e1 -null mice exhibit reduced cortical and limbic structures and pronounced retinal dystrophy. NR2E1 functions mainly as a repressor of gene transcription in association with the co-repressors atrophin-1, LSD1, HDAC and BCL11A. Recent evidence suggests that NR2E1 also acts as an activator of gene transcription. However, co-activator complexes that interact with NR2E1 have not yet been identified. In order to find potential novel co-regulators for NR2E1, we used a microarray assay for real-time analysis of co-regulator–nuclear receptor interaction (MARCoNI) that contains peptides representing interaction motifs from potential co-regulatory proteins, including known co-activator nuclear receptor box sequences (LxxLL motif). Results We found that NR2E1 binds strongly to an atrophin-1 peptide (Atro box) used as positive control and to 19 other peptides that constitute candidate NR2E1 partners. Two of these proteins, p300 and androgen receptor (AR), were further validated by reciprocal pull-down assays. The specificity of NR2E1 binding to peptides in the array was evaluated using two single amino acid variants, R274G and R276Q, which disrupted the majority of the binding interactions observed with wild-type NR2E1. The decreased binding affinity of these variants to co-regulators was further validated by pull-down assays using atrophin1 as bait. Despite the high conservation of arginine 274 in vertebrates, its reduced interactions with co-regulators were not significantin vivo as determined by retinal phenotype analysis in single-copyNr2e1 -null mice carrying the variant R274G. Conclusions We showed that MARCoNI is a specific assay to test interactions of NR2E1 with candidate co-regulators. In this way, we unveiled 19 potential co-regulator partners for NR2E1, including eight co-activators. All the candidates here identified need to be further validated usingin vitro andin vivo models. This assay was sensitive to point mutations in NR2E1 ligand binding domain making it useful to identify mutations and/or small molecules that alter binding of NR2E1 to protein partners.